Textile Dye Adsorption by Natural Perlite - Bekheira Samir; Youcef Djamel Ould; Nabil Beloufa; Abdelkader Bouhenna; Kada Boualem; Hamadache Miloud (Annals of West University of Timisoara: Physics)
In today's world of industrial progress, pollution is a major concern, especially water pollution. Considered a real danger to mankind, this article looks at the treatment of water contaminated by textile dyes, which has become a danger to humans and the environment. As an example, we have chosen the green dye FB (anionic type) which is found in the rejects of a textile factory ENADITEX in the industrial zone of the wilaya of ORAN - ALGERIA, this dye is among the most used in the textile industry. The method adopted for dye removal is adsorption by natural perlite. The Experimental results showed that adsorption of the green dye FB on the porous solid studied: natural perlite, gave a removal rate of 87.51% for 60 minutes. The adsorption isotherms of the adsorbent/adsorbate systems studied are satisfactorily described by the two mathematical models Freundlich and Temkin. All the results obtained show that the adsorption kinetics of the green dye FB by the solid material is well described by the second-order model. The adsorption reaction is a physisorption, as the thermodynamic study demonstrated.